Factors Related to Increasing the Accreditation Status of Health Centers in Konawe District - Sadaoda, Imiawati; Saafi, La Ode; Sunarsih, Sunarsih (Waluya The International Science of Health Journal, 2022)
Introduction: Data on the accreditation of the Public health center in Konawe Regency, there is still Public health center that has not been accredited and there is also no Public health center that has primary or plenary status. The purpose of this study was to analyze the factors associated with increasing the accreditation status of the Public health center in Konawe Regency. Method: This type of research is quantitative research with a cross-sectional study design. The population as many as 1032 people, with a sample size is 92 respondents. Sampling technique using Cluster Random Sampling. The data that has been collected is then analyzed using the chi-square test and the Cramer coefficient correlation test. Result: The results showed that there was a relationship between employee performance, obtained the value of X² Count > X² Count. The variable availability of human resources is the variable that is most closely related to the Cramer coefficient value of 0.917. Conclusion: The variable availability of human resources is the variable that is most closely related to increasing the accreditation status of the Public health center in Konawe Regency.